Kompetensi Pedagogis Guru Agama Buddha: Tinjauan Sistematis Literatur - Partono Nyanasuryanadi; Ellyantika Sari (Indo Publishing, 2026)
This study aims to examine the pedagogical competence of Buddhist teachers through a Systematic Literature Review (SLR) approach. Fifty authoritative journal articles published in the past five years were systematically analyzed. The results indicate that interactive teaching strategies, conducive classroom management, and assessment aligned with learning objectives contribute significantly to increased student engagement and motivation. Furthermore, the continuous development of teachers' pedagogical competence is a crucial factor in improving the quality of Buddhist learning. This study emphasizes the need to strengthen teachers' pedagogical competence to support effective and meaningful Buddhist learning.